Dynamic Characteristics Evaluation on Portable Steel Frame against Vertical Mass Irregularities - Kamarudin, Ahmad Fahmy; Ibrahim, Azmi; Mokhatar, Shahrul Niza; Zainal Abidin, Mohd Hazreek; Faisal, Ade (International Journal of Integrated Engineering, 2020)
Application of irregular mass configuration in modern design era of buildings is unavoidable in order to serve various building functionality. Discontinued and unsymmetrical mass applied on a structure could vary its dynamic behaviour. Thus, a regular geometry of 5-storey steel frame tower at 5 meter height is designed and constructed in Jamilus Research Centre laboratory, to investigate the dynamic characteristics in terms of natural frequencies and its mode shapes subjected to various mass orientations. A total of four steel blocks at 800 kg are placed in equivalent, ascending and alternating orientations on the 1st to 4th storey of the frame. Ambient vibration (AV) technique is used for dynamic characteristics evaluation. Uni-axial accelerometer sensors are aligned in bi-axial horizontal directions of North-South and East-West. ARTeMIS processing tool and Frequency Domain Decomposition (FDD) methods are used for modal parameters determination. Comparative findings are made between bare frame and mass action frame. Significant reduction of predominant frequency showed up to 37.79% between bare frame against frame in ascending mass orientation. Equivalent mass orientation shows the lowest percentage discrepancy percentage compared to others. Two translation mode shapes and torsional mode are illustrated by respective three predominant frequencies. Even though some changes have be found in predominant frequencies, but comparable mode shapes illustration are observed from all three frequency modes from all frame configurations.